AB0683 Hip Involvement in Spondyloarthritis Patients: A Frequent and Serious Manifestation. (15th July 2016) - Aguiar, F.; Martins-Rocha, T.; Fonseca, R.; Bernardo, A.; Brito, I.
Abstract : Background: The prevalence of hip involvement in spondyloarthritis (SpA) patients varies from 7–50%. It is a cause of significant functional impairment and a marker of poor prognosis. Objectives: The aim of this study was to compare demographic, clinical, laboratory and treatment data among SpA patients with and without hip involvement. Methods: Cross-sectional study including 187 SpA patients that fullfilled the modified New York criteria. The patients completed a questionnaire assessing age at diagnosis, disease subtype, clinical presentation, disease-activity (BASDAI, ASDAS) and functional-indices (BASFI) and BASMI was calculated. The patients' records were consulted to asses the following parameters: presence of HLA-B27 antigen, inflammatory markers (ESR, CRP), radiographs of spine, hip and sacroiliac joints. Hip involvement was considered based on the BASRI-hip scoring system (hip involvement if ≥2). The statistical analysis was performed using SPSS 21.0 software, and p <0.05 was taken to indicate statistical significance. To compare the differences between the groups, Mann-Whitney U, χ 2 and Fisher tests were used. Results: 187 patients were included, with 55.6% males, median age 46.0 (range 21.0–79.0) years. In this study 75 (40.1%) patients had hip involvement, which was significantly more frequent in males (46.1% vs 32.5%, p=0.041). There were no statistically significant differences in age at diagnosis, age at evaluation, time of diagnosis, smoking habits, subtype of SpA, extra-articular manifestations or HLA-B27 positivity. Ankylosis of bilateral sacroiliac joints and syndesmophytosis were significantly more frequent in patients with hip involvement (56.2 vs 28.8% p<0.001 and 57.3% vs 38.7% p=0.009). Median disease duration was significantly greater in SpA patients with hip involvement (19.0 vs 14.0 years, p=0.001). BASMI, BASFI and ASDAS-CRP were significantly higher in patients with hip involvement (median 5.0 vs 3.8, p<0.001; median 5.1 vs 3.3, p=0.001 and 2.4 vs 2.0, p=0.038, respectively). Median BASDAI and ASDAS-ESR were also higher in these patients but this difference was not statistically significant (3.3 vs 2.8, p=0.361 and 2.3 vs 2.1 p=0.318, respectively). There were no differences in what concerns SpA treatment between the two groups. Conclusions: This study shows that radiographic hip involvement is a frequent disease manifestation in SpA, and that it could be more common in male patients with long-standing disease. It also confirms that hip involvement reflects more severe disease, as it is associated with more axial damage and functional impairment. Disclosure of Interest: None declared